VULVAR ENDOMETRİOMA: OLGU SUNUMU - GEZER, Altay; İlvan, Şennur and KUMBAK, Banu and IŞILOĞLU, Haluk and EREL, Tamer (Cerrahpaşa Medical Journal, 2014)
Background and design.- Vulvar endometriosis is a very uncommon disorder. A 38-year-old woman noted a mass at a size of a walnut in the inferior aspect of right labium major for about one and a half months and she noticed no change in the size since then. The mass was excised surgically under general anesthesia and pathology reveals that it is endometriosis. With this case, we emphasized endometriosis in the differential diagnosis of vulvar tumors and tried to summarize the literature about etiopathogenesis and diagnostic/therapeutic approach of vulvar endometriosis.